Situational Leadership of Catholic Secondary School Principals in Enhancing School Achievement in Manokwari, West Papua: Contributing to SDG 4 - Imanuel Tenau; Erny Roesminingsih; Karwanto Karwanto (Journal of Current Studies in SDGs, 2026)
Objective: To analyze and describe the situational leadership styles of boarding school principals in improving school achievement at Senior High School Katolik Villanova and Senior High School Katolik Santo Arnoldus Janssen, focusing on how principals adapt leadership practices to the readiness of teachers and educational staff. Method: A qualitative approach with a multi-site study design was employed. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. Data validity was ensured through source, method, and time triangulation. Results: The findings revealed that principals implemented flexible situational leadership styles, including directing, coaching, supporting, and delegating, based on the competence and readiness of teachers and staff. Leadership extended beyond academic improvement to emphasize character formation, discipline, faith development, and communal life. Strategies such as strengthening teacher professionalism, school culture, student mentoring, and dormitory management contributed to improved academic and non-academic achievement and fostered a positive school climate. Novelty: Proposing a spiritual-oriented situational leadership model distinctive to Catholic boarding schools in West Papua by integrating faith formation, moral exemplarity, and pastoral practices into school leadership. The model contributes to SDG 4 (Quality Education) by promoting holistic student development through academic achievement, character formation, and spiritual growth.